2012
DOI: 10.18494/sam.2012.822
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Trial of Chronic Implantation of Suprachoroidal-Transretinal Stimulation System for Retinal Prosthesis

Abstract: Retinal prosthesis is an implantable medical device to reconstruct the sense of sight for blind individuals. We have been developing a new type of retinal prosthesis called suprachoroidal-transretinal stimulation (STS), whereby an electrode array is not attached to the retina directly. To evaluate the feasibility and safety of the retinal prosthesis using STS, a clinical trial was performed. We have developed an internal device for chronic implantation. It consists of a 49-channel electrode array that has 9 ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Retinal neuroprostheses aim to provide artificial vision to those suffering from profound vision loss and blindness due to inherited photoreceptor dystrophies such as retinitis pigmentosa [1] by electrically stimulating the residual retinal network to elicit visual percepts. While numerous clinical trials have shown that visual percepts can be elicited [2][3][4][5], and partial visual function such as object detection, localisation, or navigation can be restored by activating neurons in the retina [6][7][8][9][10][11][12][13][14][15][16][17], most patients have little benefit in terms of visual quality [18].Though there are potentially multiple factors including limited 7 Author to whom any correspondence should be addressed. spatial [19,20] and temporal resolution [21,22] which could be attributed to this suboptimal performance, it is argued that the indiscriminate activation of functionally-different retinal ganglion cells (RGCs) plays an important role in limiting the vision.…”
Section: Introductionmentioning
confidence: 99%
“…Retinal neuroprostheses aim to provide artificial vision to those suffering from profound vision loss and blindness due to inherited photoreceptor dystrophies such as retinitis pigmentosa [1] by electrically stimulating the residual retinal network to elicit visual percepts. While numerous clinical trials have shown that visual percepts can be elicited [2][3][4][5], and partial visual function such as object detection, localisation, or navigation can be restored by activating neurons in the retina [6][7][8][9][10][11][12][13][14][15][16][17], most patients have little benefit in terms of visual quality [18].Though there are potentially multiple factors including limited 7 Author to whom any correspondence should be addressed. spatial [19,20] and temporal resolution [21,22] which could be attributed to this suboptimal performance, it is argued that the indiscriminate activation of functionally-different retinal ganglion cells (RGCs) plays an important role in limiting the vision.…”
Section: Introductionmentioning
confidence: 99%